The effects of exogenous tyrosine supplement on spinach (Spinacia oleracea L.) cultivation under lithium stress - TURFAN, Nezahat (Mediterranean Agricultural Sciences, 2023)
In this study, the effects of exogenous Tyrosine (Tyr: 2.5 mM) application on the variations of growth rate parameters, enzymatic and non-enzymatic constituents, oxidative stress, and mineral content under lithium-applied (Li1: 6.44 mM; Li2: 19.32 mM) seedlings of the Anlani F1 spinach cultivar were investigated. Results showed that a higher Li led to a significant reduction in the growth rate parameters including shoot, root, and leaf length, the fresh weight of shoot, root, and leaf, and leaf blade sizes, whereas a lower Li dose resulted in an increase in those parameters. In contrast, the Tyr supply to the Li-applied seedlings resulted in a rise in these measured parameters. Similarly, chlorophyll and polyphenol contents and PAL, APX, CAT, POD, and SOD activities were higher in all exogenous Tyr-treated groups, including lithium-treated groups. Whilst nitrate content was higher in the Li-applied seedlings, NR activity was lower. Also, MDA and H2O2 were found to be higher in the Li-applied group, but exogenous Tyr supplements reduced their levels in the seedlings. Li, Ca, Na, Cl, Mn, Fe, Ni, Cu, and Zn accumulation were induced by Li doses and Tyr applications together with Li, but Tyr applications alone reduced all of their levels. Also, exogenous Try supplementations to the Li-applied group caused an important decline in the Li accumulation. As a result, a higher Li dose exhibited a negative effect on the growth rate, chemical constituent, and antioxidant compounds of the Anlani F1 spinach cultivar, but exogenous Tyr supplement improved those examined traits in the Li-applied seedlings.
Keywords: Chemicals; Growth; Lithium; Spinach; Tyrosine; Ziraat Mühendisliği; Agricultural Engineering